(untitled) (International Journal of Technology and Management Research, 2020)
The study explores the relevance of theoretical aspect of crowd financing by reviewing the defining literature on Pecking Order and Agency theories in details and evaluates applications of these theories based on crowdfunding. In particular, the study critically considers the key concepts of these theories and how they could be applied in practical terms. The study decides to adopt Pecking Order and the Agency theories because they provide valuable insights into the trend of crowdfunding streams available to firms. The paper primarily adds to existing literature on the broader definition of crowdfunding as a concept and then examine the relationship between this concept and its practical applications to the chosen theories. The study combines these theoretical perspectives with the practical aspects of startup companies raising finance using the crowd because a broad reading of the literature tends to point to in this direction. The key concepts of these theories are critically considered and the study is conducted in the form of review of literature and expression of opinion. Citation: author1, author2, author3. The dynamics of Pecking Order and Agency theories on crowdfunding concept as alternate finance for start-up businesses. 2020; 4(1): 1－13. Received: (February 2, 2020) Accepted: (March 31, 2020)